2009
DOI: 10.3329/jbsa.v20i2.3994
|View full text |Cite
|
Sign up to set email alerts
|

Shivering Control in Subarachnoid Block by Nalbuphine - A Comparative Study with Pethidine

Abstract: Complication during anaesthesia is inevitable but judicious start, vigilant monitoring, application of pharmacology can prevent or lessen it. Shivering is one of the complications of Subarachnoid block (SAB). To prevent shivering during SAB many techniques had so long been applied. Among them during shivering giving low dose intravenous Pethidine is so far popular in our country. As the drug is not available all the times due to legal restriction & our socioeconomic circumstances, so we studied with anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Our study results corroborate with study of Choudhury et al which had almost 100% response rate when they had used nalbuphine in the dose more than 0.08 mg/kg. [7] We have also observed that response rate of 73% and 98% when 0.06 mg/kg and 0.08 mg/kg of the study drug were used. The difference in the response rate from the previous studies where it was around 80% (6,8) may be attributed to the difference in the study population (pregnant patient in the former study and inclusion of all types of surgery in the other study).…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Our study results corroborate with study of Choudhury et al which had almost 100% response rate when they had used nalbuphine in the dose more than 0.08 mg/kg. [7] We have also observed that response rate of 73% and 98% when 0.06 mg/kg and 0.08 mg/kg of the study drug were used. The difference in the response rate from the previous studies where it was around 80% (6,8) may be attributed to the difference in the study population (pregnant patient in the former study and inclusion of all types of surgery in the other study).…”
Section: Discussionmentioning
confidence: 80%
“…[6] Another study by Wang et al concluded that both nalbuphine (0.08 mg/kg) and meperidine (0.4 mg/kg) provide a similar rapid and potent anti-shivering effect. [8] Choudhury et al in their study observed that 5 mg nalbuphine is qualitatively superior to 25 mg of meperidine for control of shivering [7] and also they had taken dose of nalbuphine of 0.086 mg/kg. So from the previous studies, it is observed that nalbuphine is effective in the dose range of 0.05 to 0.086 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations